EEG alpha asymmetry as a gender-specific predictor of outcome to acute treatment with different antidepressant medications in the randomized iSPOT-D study. Issue 1 (January 2016) - Arns, Martijn; Bruder, Gerard; Hegerl, Ulrich; Spooner, Chris; Palmer, Donna M.; Etkin, Amit; Fallahpour, Kamran; Gatt, Justine M; Hirshberg, Laurence; Gordon, Evian
Highlights: Patients with major depressive disorder do not differ from controls on frontal alpha asymmetry, occipital and frontal alpha. Tomographic differences in alpha between patients with major depressive disorder and controls are different for males and females. Right dominant frontal alpha asymmetry is associated with treatment response and remission to escitalopram and sertraline in females but not in males. Abstract: Objective: To determine whether EEG occipital alpha and frontal alpha asymmetry (FAA) distinguishes outpatients with major depression (MDD) from controls, predicts antidepressant treatment outcome, and to explore the role of gender. Methods: In the international Study to Predict Optimized Treatment in Depression (iSPOT-D), a multi-center, randomized, prospective open-label trial, 1008 MDD participants were randomized to escitalopram, sertraline or venlafaxine-extended release. The study also recruited 336 healthy controls. Treatment response was established after eight weeks and resting EEG was measured at baseline (two minutes eyes open and eyes closed). Results: No differences in EEG alpha for occipital and frontal cortex, or for FAA, were found in MDD participants compared to controls. Alpha in the occipital and frontal cortex was not associated with treatment outcome. However, a gender and drug-class interaction effect was found for FAA. Relatively greater right frontal alpha (less cortical activity) in women only was associated with a favorable response to the Selective Serotonin Reuptake Inhibitors escitalopram and sertraline. No such effect was found for venlafaxine-extended release. Conclusions: FAA does not differentiate between MDD and controls, but is associated with antidepressant treatment response and remission in a gender and drug-class specific manner. Significance: Future studies investigating EEG alpha measures in depression should a-priori stratify by gender.